Fine particles production in sand under triaxial compression - Feia, Sadok; Clain, Xavier; Canou, Jean; Sulem, Jean; Ghabezloo, Siavash (Journal of Applied Engineering Science & Technology, 2016)
An experimental study, carried out in laboratory using a triaxial apparatus, proposes to evaluate the influence of grain size, grain shape and confining stress in fine particles production in sand specimen subjected to triaxial loading. 16 triaxial tests were conducted on specimens of an initial density index of 0.90 using the pluviation technique, with three different sands and under initial confining pressure of 100, 400, 800 and 1200 kPa. The experimental results show that the fine particles production is considerably affected by confining stresses, even at low values (100 kPa), and also by grain geometry. The experimental results show also that the fine particles production increase with the strain level during the shearing test.
Keywords: Triaxial test; Granular materials; Grain breakage; Fine particles